2015
DOI: 10.1097/moo.0000000000000153
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia associated with the use of inhaled corticosteroids

Abstract: Corticosteroid inhalers are a common cause of dysphonia and their use should be investigated in any patient with laryngeal complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In summary, therefore, as far as we are aware the evidence for any recommendation for regular mouth rinsing following the use of inhaled corticosteroids is entirely empirical. 42 One might speculate that, with the increasing use of pMDI devices with HFA propellants, which deliver drugs in true solution, and the increased use of pro-drugs such as ciclesonide 43 and beclomethasone dipropionate, 44 which are metabolised to be active in the lower respiratory tract rather than the mouth, this problem, if it exists, may become less prevalent.…”
Section: Beliefs Supporting Data and Panel Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, therefore, as far as we are aware the evidence for any recommendation for regular mouth rinsing following the use of inhaled corticosteroids is entirely empirical. 42 One might speculate that, with the increasing use of pMDI devices with HFA propellants, which deliver drugs in true solution, and the increased use of pro-drugs such as ciclesonide 43 and beclomethasone dipropionate, 44 which are metabolised to be active in the lower respiratory tract rather than the mouth, this problem, if it exists, may become less prevalent.…”
Section: Beliefs Supporting Data and Panel Conclusionmentioning
confidence: 99%
“…There is in fact little clinical evidence to justify or guide such a strategy. A recent review 43 concluded that dysphonia may be improved by changing the inhaler device, or by reducing the amount and/or frequency of inhaled corticosteroid therapy, or changing the inhaled corticosteroid to ciclesonide (a small particle, true solution pro-drug not active in the upper airways).…”
Section: Beliefs Supporting Data and Panel Conclusionmentioning
confidence: 99%
“…Our results suggest that the use of ICS may be an independent risk factor for the development of OSA, especially in already at-risk patients such as overweight males. The use of ICS may produce local effects on the upper airway dilators that increase the risk of developing OSA, similar to the underlying mechanisms that increase the risk of dysphonia in ICS users [ 10 ]. The particle size of ICS likely influences this predisposition for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled corticosteroids (ICS) are known to increase the risk for dysphonia by causing myopathy of the vocal cord adductors [ 10 ]. In the same way, ICS may produce similar local effects on the upper airway dilators that could increase the risk of developing OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuation or modification of inhaled corticosteroids should be considered, if possible. 4,8 Endoscopic excision in selected cases, and pulse dye or potassium titanyl phosphate (KTP) laser to treat fungal lesions have been described as adjuncts to management. 5,9 Laryngeal cryptococcosis remains a rare cause of hoarseness.…”
mentioning
confidence: 99%